MECHANISMS FOR IMPROVING PROJECTS OF BUSINESS INCUBATORS WITHIN THE FRAMEWORK OF THE SMALL BUSINESS SUPPORT PROGRAM - Narzullaev Shodiyor (Web of Journals Publishing, 2025)
In this article, the role of business incubators within the framework of the small business support program, its historical development periods, the formation of business ideas, "Incubation" of business projects of new enterprises, the use of improved mechanisms in the implementation of the project through methods and techniques are put forward. Also, economic evaluation of business incubator projects, calculation methods of partnership projects, financial and economic indicators, results, data in the form of tables are presented. In this case, attention is paid to the initial funds for the implementation of the project, whether the investments will pay off or vice versa, and the effectiveness of the use of investment funds.
Keywords: Small business, business incubator, modeling, startup, innovation, idea, development, business, schedule, service, incubation, project, economic evaluation, partnership, financing.